Exploring the Need for Education on Cortical Visual Impairment Among Occupational Therapy Professionals and Teachers of Students With Visual Impairments. (July 2022) - Harpster, Karen; Hamilton, Sophia; Lusk, Kelly E.; Seastone, Anna M.; Fox, Amy E.; Rice, Melissa L.; Schwartz, Terry
Introduction: Cortical or cerebral visual impairment (CVI) is the leading cause of bilateral visual impairment in developed countries. The goals of this study were to explore the CVI education and training received by occupational therapy practitioners and teachers of students with visual impairments and to quantify the confidence of these professionals to evaluate and work with children who are diagnosed with CVI.Methods: An Internet-based survey was conducted with a volunteer sample that included occupational therapists, certified occupational therapy assistants, and certified teachers of students with visual impairments who practice in 50 U.S. states; Washington, D.C.; and Canada. The survey was posted on professional organizations and social media websites, as well as emailed to colleagues at organizations such as the Association for the Education and Rehabilitation of the Blind and Visually Impaired, schools for students who are blind, and local universities. Data collection occurred between June 2019 and November 2019.Results: Surveys were completed by 205 respondents from 43 U.S. states; Washington, D.C.; and Canada. Occupational therapy practitioners consistently reported lower rates of formal education in CVI, with only 25% of occupational therapists and 47% of certified occupational therapy assistants receiving education on CVI in their academic programs. Less than 23% of occupational therapists received training on CVI assessments, whereas 75% of teachers of students with visual impairments had training in CVI assessments. Additionally, respondents indicated reduced satisfaction with their knowledge and skills for treating or teaching children with CVI.Discussion: The results indicate a gap in formal CVI education for occupational therapy practitioners and, to a lesser extent, teachers of students with visual impairments. Due to the increasingly high prevalence of CVI, the gap in formal education on CVI is significant.Implications for Practitioners: Results indicate the need to increase formal and continuing education for occupational therapy practitioners and teachers of students with visual impairments.